2016
DOI: 10.2166/wrd.2016.068
|View full text |Cite
|
Sign up to set email alerts
|

Water polishing of phenol by walnut green hull as adsorbent: an insight of adsorption isotherm and kinetic

Abstract: The present paper aims to investigate water purification of phenol by walnut green hull adsorbent.The surface characteristics of the adsorbent were studied using Fourier transform infra-red (FTIR), scanning electron microscope, and X-ray diffraction (XRD) techniques. The presence of functional groups such as hydroxyl and carbonyl onto walnut green hull surface was proved by FTIR analysis. . Also, the adsorption kinetics of phenol on the adsorbent were studied. The rates of sorption were found to conform to pse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Walnut green husk as adsorbent was also examined for the removal of phenol from water [152]. The authors achieved the maximum sorption at pH 4.0, and the results indicated that the Langmuir isotherm was the appropriate model for describing the obtained data for the adsorption of phenol onto the green husk of walnut fruit.…”
Section: Walnut Husk Usesmentioning
confidence: 99%
“…Walnut green husk as adsorbent was also examined for the removal of phenol from water [152]. The authors achieved the maximum sorption at pH 4.0, and the results indicated that the Langmuir isotherm was the appropriate model for describing the obtained data for the adsorption of phenol onto the green husk of walnut fruit.…”
Section: Walnut Husk Usesmentioning
confidence: 99%
“…A lower removal efficiency under highly acidic conditions can be due to the occupation of active sites of N-HTAC by H + and H 3 O + . Under these conditions, the surface of adsorbent was protonated and was positively charged resulting in a repulsive force between adsorbate and adsorbent and excessive H + fought with Pb 2+ in the solution for an ion exchange reaction with unsaturated ions in N-HTAC [29,34]. The pH zpc (pH zero point charge ) of adsorbent is very important in the determination of optimum pH [31,35].…”
Section: Discussionmentioning
confidence: 99%
“…Phenol is a contaminant present in water derived from various chemical processes, mainly used in the manufacture of resins, cosmetics, pharmaceuticals, paints, pesticides, solvents and household cleaning products [1,2]. It is a hydroxylated derivative of benzene.…”
Section: Introductionmentioning
confidence: 99%
“…It is a hydroxylated derivative of benzene. Phenol is a white powder of high stability, great solubility and low biodegradability [1,2]. It is classified as priority hazardous pollutant by EPA [2,3].…”
Section: Introductionmentioning
confidence: 99%